Effect of Calcitriol on the Renal Microvasculature Differentiation Disturbances Induced by AT1 Blockade During Nephrogenesis in Rats - Deluque, Amanda L.; de Almeida, Lucas F.; Francescato, Heloísa D. C.; da Silva, Cleonice G. A.; Costa, Roberto S.; Antunes-Rodrigues, José; Coimbra, Terezila M. (Frontiers in Medicine, 2020)
Alterations in the renal vasculature during fetal programming can cause disturbances in renal structure and function that persist into adulthood. Calcitriol can affect cellular differentiation and proliferation, and promote endothelial cell maintenance, each of which is a key event in nephrogenesis. Calcitriol is a negative endocrine regulator of the renin gene. Rats exposed to renin-angiotensin system (RAS) antagonists during lactation have been shown to develop renal disorders, which demonstrated that the RAS may play an important role in mammalian kidney development. We evaluated the effects of calcitriol administration on losartan (angiotensin II receptor antagonist [ANGII], AT1)-induced changes in renal differentiation in rats during lactation. Rats treated with losartan showed alterations in renal function and structure that persisted into adulthood. These disruptions included hydronephrosis, papillary atrophy, endothelial dysfunction, and aberrant endothelial structure. These changes were mitigated by treatment with calcitriol. The results of our study showed that animals exposed to AT1 blockade during lactation exhibited altered renal microvasculature differentiation in adulthood that was attenuated by treatment with calcitriol.